THE DEVELOPMENT OF PQ4R STATEGY ORIENTED MATHHEMATIC STUDENTS WORKSHEET (LKS) ON THE SUBJECT MATTER TRAPEZOID AND KITE AREA FOR FIFTH GRADE STUDENTS OF ELEMENTARY SCHOOL - Apriliani, Puji Diana; Eka, Karma Iswasta; Irianto, Sony (Universitas Muhammadiyah Purwokerto, 2014)
This study employed research and development design.The aims of this study were to find out : 1) elgibility responses from expert in teacher working group (KKG) of elementary school toward PQ4R strategy oriented student worksheet on the subject matter trapezoid and kite area for fifth grade students of elementary school, 2) students and teacherâs responses toward the learning process by means of PQ4R strategy oriented student worksheet on the subject matter trapezoid and kite area for fifth grade students of elementary school. According to Thiagarajan, the process of development of student worksheet by using 4-D model is through defining (define), designing (design), developing (develop) and desseminatting (desseminat). However, in this study the process was restricted to the development process. This study yielded a PQ4R strategy oriented mathematics student worksheet on the subject mater. The students worksheet is very valid/very good/without revision according to expert (4,27) and validators (4,4), the students mostly gave positive response because have respons student 78,44% with option a, 20,44% with option b and c for 1,11% of the students said that the LKS was interesting/helpful/motivating and ispiring, and the teachers strongly agreed that the LKS was helpful. Basedon the result obtained. It is concluded the PQ4R strategy orientated mathematic student worksheet on the subject matter trapezoid and kite area for fifth grade students of elementary school can be used in learning process.Keywords :student worksheet (LKS), PQ4R strategy, research and development